2017
DOI: 10.3390/en10010064
|View full text |Cite
|
Sign up to set email alerts
|

Power Consumption Analysis of Electrical Installations at Healthcare Facility

Abstract: This paper presents a methodology for power consumption estimation considering harmonic and interharmonic content and then it is compared to the power consumption estimation commonly done by commercial equipment based on the fundamental frequency, and how they can underestimate the power consumption considering power quality disturbances (PQD). For this purpose, data of electrical activity at the electrical distribution boards in a healthcare facility is acquired for a long time period with proprietary equipme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…n/a n/a n/a n/a n/a n/a n/a n/a n/a n/a n/a n/a HCE −6. 23 Finally, Figure 8 shows the geographical distribution of the classified buildings. It is hard to identify a spatial pattern in this case, but it may be observed that class 4 buildings are located mainly in the borders (rural and mountainous areas).…”
Section: Results Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…n/a n/a n/a n/a n/a n/a n/a n/a n/a n/a n/a n/a HCE −6. 23 Finally, Figure 8 shows the geographical distribution of the classified buildings. It is hard to identify a spatial pattern in this case, but it may be observed that class 4 buildings are located mainly in the borders (rural and mountainous areas).…”
Section: Results Evaluationmentioning
confidence: 99%
“…So, the analysis of power consumption in buildings is becoming much more relevant today than in the past, when it was several orders lower than thermal demand. Moreover, monitoring can provide advanced visualization and data analysis tools to achieve energy savings and peak power optimization [22,23].…”
Section: Building Sustainability Energy Indexes and Annual Electricmentioning
confidence: 99%
“…Reference of output voltage consists of the output of fundamental control loop, output of supplementary control loop and the decoupling component [21,22], thus the voltage reference of VSC can be described as:…”
Section: Supplementary Control Loopmentioning
confidence: 99%
“…The inter-harmonics voltage can be caused by variable frequency device (VFD) or adjustable speed device (ASD), HVDC and time-varying loads [19,20]. Also, the high frequency resonance (HFR) [21,22] caused by the interconnected system consisting of the grid-connected device and parallel-compensated grid can generate the inter-harmonic voltage at PCC. According to the recommendation from IEEE, the individual inter-harmonics of voltage distortion can be no more than 1% to 5% in different voltage levels [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…According to the definition, interharmonic frequency refers to any frequency which is not a multiple of the fundamental frequency of a power supply or a frequency converter. Interharmonics attracted much attention in the past few years [3,4]. In particular, electrical engineers who study current and voltage waveform distortion in power systems are interested in interharmonics [5,6].…”
Section: Introductionmentioning
confidence: 99%